Competitive Strategies of Salafi Islam in Entrepreneurial Innovation in the Disruptive Era - Aip Nuralim Nuralim; Cecep Sastrawijaya (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2024)
The disruptive era has brought rapid changes in economic dynamics, compelling various entrepreneurial groups to adapt and innovate to maintain competitiveness. Among these groups is the Salafi Islamic community, which is often perceived as traditional and resistant to modern influences. This study explores the competitive strategies employed by Salafi Muslims in entrepreneurial innovation amidst the challenges of the disruptive era. The research addresses the following issues: How does the Salafi community integrate their religious values into entrepreneurship? What innovative strategies do they adopt to remain competitive? The aim is to uncover the intersection of religious principles and entrepreneurial practices, shedding light on their adaptability in a fast-evolving market landscape. This study employs a qualitative approach, using case studies with Salafi entrepreneurs in various business sectors. Data collection involved participant observation, and document analysis. The data were analyzed using thematic coding to identify key strategies and patterns in their approach to entrepreneurship. The findings reveal that Salafi entrepreneurs integrate Islamic principles such as fairness, trustworthiness, and social responsibility into their business models, distinguishing them from conventional practices. They adopt innovative strategies, including leveraging digital platforms for marketing, utilizing community networks for business expansion, and focusing on niche markets aligned with their religious values. These strategies demonstrate their ability to balance traditional principles with modern entrepreneurial demands, ensuring sustainability and relevance in the disruptive era. This study contributes to understanding how religious communities can thrive in contemporary economic contexts by aligning spiritual values with strategic business practices